Odpowiedzi

2010-02-13T20:57:03+01:00
2x+3y/5x-y = 1,25 | * 5
6(x+1)^2-2(x-y)^2=2(y-5)^2+4xy+48
10x + 3x + y - y = 6,25
(6x + 6)^2 - (2x - 2y)^2 = (2y - 10)^2 + 4xy + 48
13x = 6,25
8,5x + 8 - 2x - 2y = 2y - 10 + 4xy + 48
13x = 6,25
6,5x + 8 - 2y = 2y - 10 + 4xy + 48
13x = 6,25
6,5x + 8 = 4y - 10 + 4xy + 48
13x = 6,25
6,5x + 8 - 48 = 4y - 10 - 4xy
13x = 6,25
6,5x - 40 + 10 = 4y - 4xy
13x = 6,25
6,5x - 30 = 4y - 4xy
13x = 6,5
6,5x = 4y - 4xy + 30 | * 2
13x = 6,5
13x = 8y - 8xy + 60
0 = 6,5
ODP. : równanie jest sprzeczne , czyli nie ma rozwiązania .